Rusli, R., Asdar, M., & Munir, A. R. (2019). Strategi Pengelolaan dan Pengembangan Industri Perumahan Kelas Menengah (Studi Kasus PT. Baruga Asrinusa Development). Hasanuddin Journal of Applied Business and Entrepreneurship, 2(3), 124-136. - Manjappai Daeng Bella; Abdul Rahman Kadir; Andi Ratna Sari Dewi (Hasanuddin Journal of Applied Business and Entrepreneurship, 2019)
This study aims to determine the level of perception / expectation and business performance, business strategy and core business development strategy for PT. Fishery Archipelago (Persero). Research done at PT. Perikanan Nusantara (Persero) by analyzing the business strategy that has been implemented perusahaan. Langkah first research to know the vision, mission, and the motto of the company. Early phases of researchers to analyze IPA (Importance Performance Analysis) and then continued by doing GAP analysis, the analysis is part of the IPA analysis. A positive GAP (+) will be obtained if the perception score is greater than the expectation score, whereas if the expectation score is greater than the perception score will be GAP (-) negative. The results of this study found that business strategies that can be implemented by PT Fishery Nusantara (Persero), among others, Improving the quality of human resources in the field of planning, production and marketing; increasing the quantity and quality of monitoring and evaluation on company performance and efforts to improve government policy support; improving product quality with promotional strategies and appropriate pricing to face competition; as well as improvement of internal management quality, improvement of managerial structure and reward and punishment mechanism to face bargaining power of buyer and supplier.